The impact of human papillomavirus (HPV) status on functional outcomes and quality of life (QOL) after surgical treatment of oropharyngeal carcinoma with free-flap reconstruction - Hani Z. Marzouki; Vincent L. Biron; Peter T. Dziegielewski; Andrew Ma; Jason Vaz; Gabriela Constantinescu; Jeffrey Harris; Daniel O’Connell; Hadi Seikaly (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background To determine the impact of Human Papillomavirus (HPV) status on speech, swallowing, and quality of life (QOL) outcomes after surgical treatment of oropharyngeal cancer (OPSCC). Methods A retrospective review of a prospectively collected database of all patients with OPSCC diagnosed and treated from 1998 to 2009. Speech, swallowing, and quality of life data were gathered at 3 different evaluation points. HPV status was determined using p16 positivity as a surrogate marker. Univariate and multivariate statistical analyses were performed to identify whether p16 status is a significant predictor of functional outcome and QOL. Results One hundred twelve patients with OPSCC and known p16 status were treated with primary surgery between 1998 and 2009, with mean age of 56 years. Out of those patients 63 (56%) were p16 positive. Speech intelligibility remained high at 1-year post operation (95.4%). Only 11.5% of the patients required a feeding tube at 1 year after surgery to maintain their daily caloric requirements and the risk of aspiration after surgery was not significant (p = 0.097). There was no statistically or clinically significant difference in speech, swallowing ability, swallowing safety and QOL outcomes between p16-positive and negative OPSCC. Conclusions Surgically treated OPSCC patients demonstrate excellent swallowing function and can achieve excellent speech perception. P16 status may not be predictive of functional outcomes or QOL in surgically treated OPSCC.